Successful franchising - Sugars, Bradley J. (McGraw-Hill, 2006)
A multimillionaire who built Action International up from a home-based operation to the 16th fastest growing franchise in the world in just twelve years, with nearly 1,000 franchises worldwide, Brad Sugars is one of the most successful franchising experts in the world. With the help of real-life examples, including KFC, Subway, and Howard Johnson's, Sugars arms you with powerful information you can put into action-immediately. You'll discover: Everything you need to know about buying a franchise. How to franchise your own business . The pros and cons of franchising versus licensing. Insider tips for selling a franchise